A highly efficient vortex-assisted liquid–liquid microextraction based on natural deep eutectic solvent for the determination of Sudan I in food samples. Issue 30 (4th June 2019) - Liu, Wei; Zong, Bingyue; Wang, Xiaoping; Cai, Junlan; Yu, Jingjing
Abstract : A highly efficient vortex-assisted liquid–liquid microextraction based on natural deep eutectic solvent was developed for the determination of Sudan I. Abstract : A natural deep eutectic solvent (NADES) composed of choline chloride (ChCl) and sesamol was successfully employed in the vortex-assisted liquid–liquid microextraction (VALLME) of food toxicant Sudan I (1-phenylazo-2-naphthalenol) in food samples for HPLC-UV analysis. Sesamol-based NADESs exhibited better Sudan I extraction abilities than other deep eutectic solvents and conventional organic solvents. 1 H NMR and 2D NOESY spectra were used to characterize the sesamol-based NADESs, indicating that hydrogen bonds were formed between ChCl and sesamol. The developed VALLME method showed a high extraction efficiency (near 100%) within 60 s at room temperature. Under the optimized extraction conditions, this established method showed good linearity ( r 2 = 1.000) and a low limit of detection (LOD) of 0.02 mg kg −1 . The recoveries were in the range of 93–118%, and the intra-day and inter-day precisions were less than 4.5%. The developed method was successfully applied to the determination of Sudan I in various food samples, including chili oil, chili sauce, and duck egg yolk. This method gave a higher recovery than that of the EU recommended method when applied to sample analysis.